Fundamentalism and fanaticism: a comparative analysis - Yousif, Ahmad (Equinox Publishing Ltd., 2011)
Despite the fact that fanaticism exists in world religions, there has been a strong tendency to associate Islam with fundamentalism and fanaticism. Consequently, many scholars view the terms as almost synonymous. What exactly is fanaticism and what are some of the reasons for its occurrence? If all the world’s great religions preach peace and the preservation of life, why do fanatics kill and maim in the name of their religion? How did this term come to be closely associated with Islam rather than other major world religions, and most particularly in the last three decades? Is this connection justified academically or otherwise? What have contemporary and classical Muslim scholars written about the above terms? This paper will address the above questions, including the concept of “fanaticism” and “fundamentalism,” the relationship between fanaticism and Islamic revivalism, and whether fanaticism can be “cured.”